AN ANALYSIS THE CHARACTER OF FORREST GUMP MOVIE BY ROBERT ZEMECKIS VIEWED FROM BIG FIVE PERSONALITY TRAITS THEORY - Dwi Sakti Manggalasari; Dian Luthfiyati (Universitas Islam Lamongan, 2018)
The purpose of this research is to know the character and characterization of Forrest Gump as main character in the movie by analyzing the evidence from the dialogues and his actions in the movie. To know what the character and characterization of Forrest, the writer used the method descriptive-qualitative. The writer employs himself to collect the data by reading script, watching the movie and classifying them. The writer focused the dialogues of the movie, and then followed by classifying and analyzing the character and characterization through the big five personality theory The writer found that The Character in the movie are Forrest as Protagonist Character and Forrest as mayor Character. The Forrest character in the movie viewed the Big Five personality, Forrest have all the type of the character such as Openness, Contentiousness, Extraversion or Introversion, Agreeableness, and Neuroticism, but the dominate of Forrest character is Agreeableness. Forrest have high agreeableness, he have the character flexible, trusting, cooperative, forgiving, empathic, soft-hearted, tolerant. Keywords: Character, big five personality